ANALYSIS OF THE NEEDS OF TERMINAL AREA 1 JUANDA INTERNATIONAL AIRPORT SURABAYA - Satya Adi Wicaksana, Yusuf; Suryono, Wiwid; Rozi, Fahrur (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Juanda Surabaya International Airport has terminal 1 and terminal 2. The total area of terminal 1 is 91,700 m2. In 2014 the number of passengers reached 17,285,070 and experienced an increase in the number of passengers for 4 years until 2018 reached 20,951,063. With the increasing number of passengers at Juanda Airport and serving Umrah and Hajj flights, the terminal area will not be able to accommodate passengers in the next 20 years. Forecasting the number of passengers for the next 20 years using the linear regression method with software. The results of passenger forecasting in 2043 reached a total of 51,393,285 passengers. The number of transfer passengers is 3,597, the number of peak hour passengers is 17,988, the number of arriving and departing peak hour passengers is the same at 7,195. The 2043 terminal needs analysis is calculated based on SKEP/VI/77/2005 using the number of peak hour passengers. While the total results of the analysis of terminal space requirements at Juanda International Airport Surabaya, the area of passenger terminal facilities amounted to 53,730m2. To overcome the anticipated capacity of the number of passengers at peak hours in 2043.